The Intention to Use Signal Application for Paying Motor Vehicle Taxes - Suci, Nanda Destyana; Bangsawan, Satria; Pandjaitan, Dorothy Rouly H. (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
In this digital age, governments are increasingly embracing online payment of car taxes and other public services made possible by advances in information technology. A digital software called SIGNAL was created to make it easier to validate car registrations and tax payments online. The lower utilization rate compared to traditional services at Samsat offices indicates that its implementation is still unsatisfactory, especially in Lampung Province. The purpose of this research is to use an expanded Technology Acceptance Model (TAM) to determine what variables impact taxpayers' intent to utilize the SIGNAL application. Perceived safety, trust, and subjective standards are some of the extraneous factors included in the model. Data was collected from 120 participants chosen at random using a survey approach. Partial Least Squares (PLS) analysis using SmartPLS software was used to examine the data. Findings show that the desire to use the SIGNAL app is heavily impacted by subjective norms, perceived security, perceived trust, perceived simplicity of use, and perceived utility. The public sector may improve its plans for adopting digital services by using the insights provided by these studies.